Elementary Functions - 4.22 Infinite Products and Partial Fractions

From testwiki
Revision as of 11:07, 28 June 2021 by Admin (talk | contribs) (Admin moved page Main Page to Verifying DLMF with Maple and Mathematica)
(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)
Jump to navigation Jump to search


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
4.22.E1 sin z = z n = 1 ( 1 - z 2 n 2 π 2 ) 𝑧 𝑧 superscript subscript product 𝑛 1 1 superscript 𝑧 2 superscript 𝑛 2 superscript 𝜋 2 {\displaystyle{\displaystyle\sin z=z\prod_{n=1}^{\infty}\left(1-\frac{z^{2}}{n% ^{2}\pi^{2}}\right)}}
\sin@@{z} = z\prod_{n=1}^{\infty}\left(1-\frac{z^{2}}{n^{2}\pi^{2}}\right)

sin(z) = z*product(1 -((z)^(2))/((n)^(2)* (Pi)^(2)), n = 1..infinity)
Sin[z] == z*Product[1 -Divide[(z)^(2),(n)^(2)* (Pi)^(2)], {n, 1, Infinity}, GenerateConditions->None]
Successful Successful - Successful [Tested: 7]
4.22.E2 cos z = n = 1 ( 1 - 4 z 2 ( 2 n - 1 ) 2 π 2 ) 𝑧 superscript subscript product 𝑛 1 1 4 superscript 𝑧 2 superscript 2 𝑛 1 2 superscript 𝜋 2 {\displaystyle{\displaystyle\cos z=\prod_{n=1}^{\infty}\left(1-\frac{4z^{2}}{(% 2n-1)^{2}\pi^{2}}\right)}}
\cos@@{z} = \prod_{n=1}^{\infty}\left(1-\frac{4z^{2}}{(2n-1)^{2}\pi^{2}}\right)

cos(z) = product(1 -(4*(z)^(2))/((2*n - 1)^(2)* (Pi)^(2)), n = 1..infinity)
Cos[z] == Product[1 -Divide[4*(z)^(2),(2*n - 1)^(2)* (Pi)^(2)], {n, 1, Infinity}, GenerateConditions->None]
Successful Successful - Successful [Tested: 7]
4.22.E3 cot z = 1 z + 2 z n = 1 1 z 2 - n 2 π 2 𝑧 1 𝑧 2 𝑧 superscript subscript 𝑛 1 1 superscript 𝑧 2 superscript 𝑛 2 superscript 𝜋 2 {\displaystyle{\displaystyle\cot z=\frac{1}{z}+2z\sum_{n=1}^{\infty}\frac{1}{z% ^{2}-n^{2}\pi^{2}}}}
\cot@@{z} = \frac{1}{z}+2z\sum_{n=1}^{\infty}\frac{1}{z^{2}-n^{2}\pi^{2}}

cot(z) = (1)/(z)+ 2*z*sum((1)/((z)^(2)- (n)^(2)* (Pi)^(2)), n = 1..infinity)
Cot[z] == Divide[1,z]+ 2*z*Sum[Divide[1,(z)^(2)- (n)^(2)* (Pi)^(2)], {n, 1, Infinity}, GenerateConditions->None]
Failure Successful Successful [Tested: 7] Successful [Tested: 7]
4.22.E4 csc 2 z = n = - 1 ( z - n π ) 2 2 𝑧 superscript subscript 𝑛 1 superscript 𝑧 𝑛 𝜋 2 {\displaystyle{\displaystyle{\csc^{2}}z=\sum_{n=-\infty}^{\infty}\frac{1}{(z-n% \pi)^{2}}}}
\csc^{2}@@{z} = \sum_{n=-\infty}^{\infty}\frac{1}{(z-n\pi)^{2}}

(csc(z))^(2) = sum((1)/((z - n*Pi)^(2)), n = - infinity..infinity)
(Csc[z])^(2) == Sum[Divide[1,(z - n*Pi)^(2)], {n, - Infinity, Infinity}, GenerateConditions->None]
Failure Successful Successful [Tested: 7] Successful [Tested: 7]
4.22.E5 csc z = 1 z + 2 z n = 1 ( - 1 ) n z 2 - n 2 π 2 𝑧 1 𝑧 2 𝑧 superscript subscript 𝑛 1 superscript 1 𝑛 superscript 𝑧 2 superscript 𝑛 2 superscript 𝜋 2 {\displaystyle{\displaystyle\csc z=\frac{1}{z}+2z\sum_{n=1}^{\infty}\frac{(-1)% ^{n}}{z^{2}-n^{2}\pi^{2}}}}
\csc@@{z} = \frac{1}{z}+2z\sum_{n=1}^{\infty}\frac{(-1)^{n}}{z^{2}-n^{2}\pi^{2}}

csc(z) = (1)/(z)+ 2*z*sum(((- 1)^(n))/((z)^(2)- (n)^(2)* (Pi)^(2)), n = 1..infinity)
Csc[z] == Divide[1,z]+ 2*z*Sum[Divide[(- 1)^(n),(z)^(2)- (n)^(2)* (Pi)^(2)], {n, 1, Infinity}, GenerateConditions->None]
Successful Successful - Successful [Tested: 7]